Effects of Rumen Protozoa of Brahman Heifers and Nitrate on Fermentation and In vitro Methane Production - Nguyen, S. H. (Asian-Australas J Anim Sci, 2016)
Two experiments were conducted assessing the effects of presence or absence of rumen protozoa and dietary nitrate addition on rumen fermentation characteristics and in vitro methane production in Brahman heifers. The first experiment assessed changes in rumen fermentation pattern and in vitro methane production post-refaunation and the second experiment investigated whether addition of nitrate to the incubation would give rise to methane mitigation additional to that contributed by defaunation. Ten Brahman heifers were progressively adapted to a diet containing 4.5% coconut oil distillate for 18 d and then all heifers were defaunated using sodium 1-(2-sulfonatooxyethoxy) dodecane (Empicol). After 15 d, the heifers were given a second dose of Empicol. Fifteen days after the second dosing, all heifers were allocated to defaunated or refaunated groups by stratified randomisation, and the experiment commenced (d 0). On d 0, an oral dose of rumen fluid collected from unrelated faunated cattle was used to inoculate 5 heifers and form a refaunated group so that the effects of re-establishment of protozoa on fermentation characteristics could be investigated. Samples of rumen fluid collected from each animal using oesophageal intubation before feeding on d 0, 7, 14, and 21 were incubated for in vitro methane production. On d 35, 2% nitrate (as NaNO(3)) was included in in vitro incubations to test for additivity of nitrate and absence of protozoa effects on fermentation and methane production. It was concluded that increasing protozoal numbers were associated with increased methane production in refaunated heifers 7, 14, and 21 d after refaunation. Methane production rate was significantly higher from refaunated heifers than from defaunated heifers 35 d after refaunation. Concentration and proportions of major volatile fatty acids, however, were not affected by protozoal treatments. There is scope for further reducing methane output through combining defaunation and dietary nitrate as the addition of nitrate in the defaunated heifers resulted in 86% reduction in methane production in vitro.